Berberine Hydrochloride-loaded Liposomes Gel: Preparation, Characterization and Antioxidant Activity - Wang, Mengmeng; Xia, Hongmei; Yang, Xinying; Zhang, Qin; Li, Yufan; Wang, Yu; Xia, Ying; Xie, Zili (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: Berberine hydrochloride is a Traditional Chinese Medicine component with antibacterial, antiviral, anti-inflammatory, antioxidant and lowering blood sugar effects. However, the application of berberine hydrochloride has been hindered for a long time due to its poor solubility and low bioavailability. This study aims to design a liposomes-gel to enhance the bioavailability and antioxidant activity of berberine hydrochloride. Materials and Methods: The thin-film dispersion hydration method was used to prepare liposomes, and liposomes-gel was prepared by the natural swelling method using sodium alginate as the hydrogel matrix. Berberine hydrochloride-loaded liposomes-gel was characterized by the encapsulation efficiency, particle size, potential, and transmission electron microscopy, and studied by in vitro release and antioxidant activity of the preparations. Results: The results revealed the encapsulation efficiency of berberine hydrochloride-loaded liposomes was 79.62±4.20% and the mean particle size was 153.7±11.2 nm. The release of berberine hydrochloride from liposomes-gel conformed to a first-order release model. The scavenging rate of DPPH free radicals and H2O2 by berberine hydrochloride-loaded liposomes-gel exceeds 70%. Conclusion: The liposomes-gel has a sustained-release effect on berberine hydrochloride. Berberine hydrochloride-loaded liposomes-gel had good antioxidant properties by measuring the scavenging ability on DPPH free radicals, H2O2 and lipid peroxidation resistance.
Keywords: Berberine hydrochloride; Liposomes; Sodium alginate; Hydrogel; Antioxidant